1993
DOI: 10.1007/bf01280835
|View full text |Cite
|
Sign up to set email alerts
|

Activation cross sections and isomeric ratios in reactions induced by 14.5 MeV neutrons on152Sm,154Sm and178Hf

Abstract: Abstract.Cross sections for the reactions zS2Sm(n ' p)152g, ml,m2pm ' 154Sm(n ' p)154g, mpm ' lVSHf(n ' p)17Sm, g Lu, 154Sm(n, d)153pm and 152Sm(n, c~)149Nd were measured at 14.5 MeV neutron energy by the activation method. On the basis of these cross sections, the associated isomeric ratios in ~Sapm, x52pm, 178Lu and the comparison with the predictions of different compound and precompound models, conclusions are drawn about the role of the preequilibrium processes in 14.5 MeV neutron induced reactions. Calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…We can see from table 2 and figure 7 that the fitting line of our experimental values, within experimental error, is consistent with the fitting line of Murahira et al [19] around the neutron energy of 14 MeV, which is much lower than the theoretical excitation curve. The values of Kirov et al [17] and Meason et al [18] , within experimental error, are consistent with those of the theoretical excitation curve at the corresponding energies, which are much higher than the values of the fitting line of our experimental values at the corresponding energies.…”
Section: Hf(n P) 178m Lu Reactionsupporting
confidence: 91%
See 1 more Smart Citation
“…We can see from table 2 and figure 7 that the fitting line of our experimental values, within experimental error, is consistent with the fitting line of Murahira et al [19] around the neutron energy of 14 MeV, which is much lower than the theoretical excitation curve. The values of Kirov et al [17] and Meason et al [18] , within experimental error, are consistent with those of the theoretical excitation curve at the corresponding energies, which are much higher than the values of the fitting line of our experimental values at the corresponding energies.…”
Section: Hf(n P) 178m Lu Reactionsupporting
confidence: 91%
“…However, until now, only a few laboratories (two to five) reported the experimental cross-section data on hafnium isotopes around the neutron energy of 14 MeV and most of them are at single neutron energy and there was disagreement in those data, which can be found in experimental nuclear reaction data (EXFOR) [1], except for the 176 Hf(n, 2n) 175 Hf reaction whose cross-section data have been reported by as many as ten laboratories [2][3][4][5][6][7][8][9][10][11]. For example, for the 174 Hf(n, 2n) 173 Hf reaction, we found just five laboratories [2-4, 12, 13] reported the experimental cross-section data induced by neutrons from the D-T reaction and all of them have only one cross-section value at single neutron energy; for the 178 Hf(n, α) 175m+g Yb reaction, we found just four laboratories [2,[14][15][16] reported the experimental cross-section data induced by neutrons from the D-T reaction and three of them have only one cross-section datum at single neutron energy; for the 178 Hf(n, p) 178g Lu reaction, we found just two laboratories [17,18] reported the experimental cross-section data induced by neutrons from the D-T reaction and both of them have only one cross-section datum at single neutron energy; for the 178 Hf(n, p) 178m Lu reaction, we found just three laboratories [17][18][19] reported the experimental cross-section data induced by neutrons from the D-T reaction and two of them have only one cross-section datum at single neutron energy; for the 180 Hf(n, 2n) 179m2 Hf reaction, we found just four laboratories [3,8,14,20] reported the experimental cross-section data induced by neutrons from the D-T reaction and three of them have only one cross-section datum at single neutron energy; for the 180 Hf(n, α) 177m+g Yb reaction, we found just four laboratories [2,4,14,15] reported the experimental cross-se...…”
Section: Introductionmentioning
confidence: 99%
“…From Figure 8 it can be seen that over the neutron energies 13.5 to 14.8 MeV, our cross section values are in agreement with the theoretical data of TALYS-1.6 and EMPIRE-3.2 codes within experimental uncertainty, but the present results and theoretical data are lower than the values of the literature [6,7,12,14,15,19,20]. At the neutron energy of 13.5 MeV, our result gives the first reported value.…”
Section: Sm(n ) 149 Nd Reactionsupporting
confidence: 88%
“…In the case of 152 Sm(n, ) 149 Nd reaction, six earlier measurements could be found in the literature [6,7,12,14,15,19,20] and all earlier data are only at one energy point. From Figure 8 it can be seen that over the neutron energies 13.5 to 14.8 MeV, our cross section values are in agreement with the theoretical data of TALYS-1.6 and EMPIRE-3.2 codes within experimental uncertainty, but the present results and theoretical data are lower than the values of the literature [6,7,12,14,15,19,20].…”
Section: Sm(n ) 149 Nd Reactionmentioning
confidence: 96%
“…Examples of such nuclides for the (n, p) reaction are 64Ni, I~176 165H0, 2~ and 2~ [7]. Some examples of such difficult or previously inaccurate measurements that have been made recently may be found in [11,12], and recent measurements of (n, p) cross sections for Sm isotopes [ 13 ] have shown that global formulae such as (19) can be used to obtain a reliable estimate of the cross section of interest.…”
Section: A(na)=fl(a~/3+ L)2exp I~l (N-z+ I )mentioning
confidence: 99%